Developing a Taxonomy of Dark Triad Triggers at Work – A Grounded Theory Study Protocol - Nübold, Annika; Bader, Josef; Bozin, Nera; Depala, Romil; Eidast, Helena; Johannessen, Elisabeth A.; Prinz, Gerhard (Frontiers in Psychology, 2017)
In past years, research and corporate scandals have evidenced the destructive effects of the dark triad at work, consisting of narcissism (extreme self-centeredness), psychopathy (lack of empathy and remorse) and Machiavellianism (a sense of duplicity and manipulativeness). The dark triad dimensions have typically been conceptualized as stable personality traits, ignoring the accumulating evidence that momentary personality expressions – personality states – may change due to the characteristics of the situation. The present research protocol describes a qualitative study that aims to identify triggers of dark triad states at work by following a grounded theory approach using semi-structured interviews. By building a comprehensive categorization of dark triad triggers at work scholars may study these triggers in a parsimonious and structured way and organizations may derive more effective interventions to buffer or prevent the detrimental effects of dark personality at work.